Incidence rate of alcohol use disorder and correlation between metabolic changes and addictive behavior in patients after sleeve gastrectomy - Wang, Fuqin; Fan, Youjie; Li, Jianhua; Yan, Jingwang; Li, Zhiyong (Frontiers in Psychiatry, 2025)
AimTo compare the incidence of AUD and correlation between metabolic changes and addictive behaviors in patients who underwent SG.MethodsA retrospective study was conducted on 160 obese patients who underwent SG treatment at our hospital between February 2023 and April 2024 (SG group), and another 160 non-surgical obese patients admitted during the same period were selected as the control group. The Alcohol Use Disorders Identification Test (AUDIT)was used to assess the risk of AUD in both groups (AUDIT≥eight points defined as high risk) and to compare the differences in high-risk rates between the groups. Differences in impulsivity scores (Barratt Impulsivity Scale [BIS]-11), addictive behavior scores(Visual Analog Scale for Addictive Behaviors[VAS]),and glucose-fat metabolism indexes between the high-and low-risk AUD subgroups within the SG group were analyzed using Pearson correlation and multiple regression analyses to explore associations between metabolic indicators and addictive behavior scores.ResultsThe SG group had a higher rate of alcohol use disorder (AUDIT ≥ 8 points) after surgery than the control group (26.88% vs. 8.125%) (χ² = 19.32, P < 0.001).The impulsivity score[BIS-11:(68.43 ± 9.35)points vs.(61.22 ± 8.71)points] and addictive behavior score[VAS:(6.42 ± 1.14)points vs.(3.88 ± 1.06)points]were significantly higher in the high-risk group than in the low-risk group(P<0.001).Fasting plasma glucose, glycated hemoglobin, and homeostasis model assessment of insulin resistance levels were significantly higher in the AUDIT high-risk group than in the low-risk group(P<0.001).lipoprotein cholesterol (TC, TG, LDL-C, HDL-C) did not differ significantly between high- and low-risk groups (P > 0.05).Glucose metabolism indices(fasting plasma glucose, glycated hemoglobin, and homeostasis model assessment of insulin resistance)were strongly and positively correlated with AUDIT and VAS scores(r=0.682–0.716,P<0.05).However, multivariate linear regression analysis indicated that impulsivity, addictive behavior propensity, and glucose metabolism abnormalities were not independently associated with statistical significance(P>0.05).The propensity for addictive behavior and abnormal glucose metabolism remained independent risk factors for AUD after SG(P<0.05),and the risk was significantly higher in men than in women. This age group had significantly higher AUDIT high-risk rates, BIS-11 impulsivity, and VAS addiction behavior scores vs. the >25 group (P<0.05).ConclusionCompared to nonsurgical patients with obesity, patients with obesity who underwent SG exhibited a significantly high incidence of AUD. Patients in the high-risk subgroup for AUD also showed high impulsivity scores, greater addictive behavior scores, and notable abnormalities in glucose metabolism indices.